2023
DOI: 10.1093/jee/toad102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of artificial diet rearing during all instars on silk secretion and gene transcription in Bombyx mori (Lepidoptera: Bombycidae)

Abstract: Silkworms (Bombyx mori) reared on artificial diets during all instars have the advantages of simplicity and efficiency, year-round production, and reduced risk of poisoning. However, low silk yield remains a challenge, limiting its industrial application. To address this issue, the spinning behavior, nutrient absorption, and transcriptomics of silkworms were investigated. Compared with silkworms reared on mulberry leaves during all instars, those fed with artificial diets showed significantly lower cocoon weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The biological and economic parameters of the B. mori larvae and adults that were fed with an artificial diet were assessed in the November-December period. Yin et al (2023) argued that feeding the silkworms with an artificial diet negatively impacts some of their traits, therefore affecting their economic value. Even by supplementing the artificial diet with bee pollen, the measured parameters were not significantly improved (Moise et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The biological and economic parameters of the B. mori larvae and adults that were fed with an artificial diet were assessed in the November-December period. Yin et al (2023) argued that feeding the silkworms with an artificial diet negatively impacts some of their traits, therefore affecting their economic value. Even by supplementing the artificial diet with bee pollen, the measured parameters were not significantly improved (Moise et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…One of the consequences is that artificial diets have been proposed as suitable alternatives. Even though the artificial diet has gained greater acceptance in recent years, studies have revealed that the development of silkworms has been affected [106]. It has been shown that mulberry leaves have a higher nutritional content than any artificial diet [40].…”
Section: Requirements Of Silkworm Larvaementioning
confidence: 99%
“…In order to improve production efficiency, modern sericulture has gradually started using artificial diets (ADs) as a substitute for MLs in silkworm rearing [15]. However, silkworms fed on ADs exhibit significantly diminished robustness and silk production efficiency [16,17]. Studies using mice and other models have revealed that a high-fat diet (HFD) or high-sugar diet (HSD) significantly affects the composition and function of the gut microbiota, thus impairing the host's metabolic homeostasis [18,19].…”
Section: Introductionmentioning
confidence: 99%